CONSUMER PREFERENCES IN ECO-TOURISM DEVELOPMENT IN BALI WITH UGC (USER GENERATED CONTENT) APPROACH - Annisa Vira Widayanti; Agustina Shinta Hartati Wahyuningtyas; Febriananda Faizal (Socio-Economics/Agribusiness Department, 2023)
The concept of ecology-based tourism or ecotourism is the main attraction for tourists. This study was conducted to determine the attributes of superior ecotourism at resorts based on consumer preferences using the UGC (User Generated Content) approach. This study was use a non-probability sampling approach and the data analysis technique was the Jaccard Score, Z-Score and PCA rankings. The results show that ecotourism attributes that are consumer preferences based on UGC include natural beauty, accessibility, atmosphere, food and beverages, and service. In addition, the ranking of superior ecotourism attributes based on consumer preferences with a jaccard score coefficient from each resort, has a different rating. This rating also applies to the results of the binomial z-score test analysis which shows the level of consumer satisfaction with these attributes. Based on the PCA analysis, it was found that the resort hotel that has the potential to compete is between Legian and Oberoi. Resorts that have competitive potential are able to improve performance based on two main components formed from the PCA analysis, namely basic and advanced offers. The greater value of this coefficient means that the attribute has a large effect on improving performance and has an effect on resort decision making.